Studi Komparatif Latihan Over Barrier Hop dan Single Leg Hop terhadap Frekuensi Tendangan Depan Atlet Tapak Suci - Hidayat, Rahmat; Muhaimin, Ali; Kesuma, Dadang Warta Chanra Wijaya (Empiricism Journal, 2025)
This study compared the effectiveness of two plyometric modalities Over Barrier Hop (OBH) and Single Leg Hop (SLH) in improving front-kick frequency among adolescent pencak silat athletes while accounting for baseline leg-power strata. Twenty-four athletes completed a four-week intervention (three sessions per week) and underwent pre–post assessments of front-kick frequency and lower-limb power. Descriptively, both groups improved after training, confirming the utility of short-term plyometrics for kick-related performance. Two-way ANOVA revealed no significant interaction between training modality and initial leg-power level and no statistically significant main effect of modality; however, the practical magnitude of the training effect was moderate-to-large, with higher estimated marginal means favoring SLH over OBH. These findings align with the mechanistic rationale and prior evidence supporting unilateral plyometrics to enhance neuromuscular control, reduce inter-limb asymmetry, and improve rate of force development relevant to kick cadence. The absence of an interaction suggests that, within a short time frame, relative benefits of both modalities are broadly similar across leg-power strata. Practically, coaches should combine unilateral and bilateral drills, implement progressive loading, and integrate strength and technique sessions to maximize transfer. Future randomized factorial trials with larger samples, longer interventions, and validated performance metrics (e.g., CMJ/RSI, ground-reaction asymmetry) are warranted to delineate modality superiority and optimize dose–response relationships.